Chronic glomerulonephritis associated with hepatosplenic Schistosomiasis Mansoni - Ramos, Eduardo Antônio Gonçalves (1987)
Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil